Some new neutrosophic normed sequence spaces defined by Jordan totient operator - Khan, Vakeel A.; Et, Mikail; Faisal, Mohd. (Univ Nis, Fac Sci Math, 2023)
In 2020 Ilkhan et al. [10] defined Jordan's totient matrix operator. In this paper, the Jordan totient matrix operator Ar and I - convergence are used to define two new sequence spaces, CI0(& phi;,& psi;,?)(Ar) and CI (& phi;,& psi;,?)(Ar), as the domain of the Jordan totient matrix operator Ar with respect to the neutrosophic norm. Some results about these sequence spaces are also studied.
Keywords: Statistical convergence; I-convergence; Jordan I-convergence